KUALITAS AIR MANGROVE DITINJAU DARI SIFAT FISIK-KIMIA DI HUTAN MANGROVE PATUNG NGURAH RAI TUBAN DENPASAR SELATAN BALI - Suriani, Ni Luh (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 3 No 1)
The objectives of this research are to find out of mangrove water quality at Patung Ngurah Rai Tuban Denpasar Selatan Bali regarding to physical-chemical . Values of some variables such as total disolved solid, Cromium (Cr), Cadmium (Cd), , Nitrit, and oil was higher than that of standard quality.This is caused by organic and anorganic waste such as garment factory come from Badung River, domestic waste, Ngurah Rai iar Port waste, and car workshop. The inpact of this problem is that the species of mangrove forest is not good condition.
Keywords: Mangrove, Contamination, Waste